TAPHONOMY, CRONOSTRATIGRAPHY AND PALEOCEANOGRAPHIC IMPLICATIONS AT TURBIDITE OF EARLY PALEOGENE (VERTIENTES FORMATION), CUBA - Menéndez, Leidy; Rojas Consuegra, Reinaldo; Villegas Martín, Jorge; López, Rafael A. (Revista Geológica de América Central, 2016)
This study focuses on the taphonomy, paleontology, and invertebrate diversity of the Upper Paleocene to Lower Eocene, turbidite deposits of Vertientes Formation, northwest of Ciego de Ávila, Central Cuba. The section exposed is stratified with detritic rocks, heterogeneous litoclasts and bioclasts. The fossil assemblage includes bivalve mollusks, gastropods, equinoderms, corals, crustaceans, icnofossils, orbitoidal foraminifera, ostracods and radiolarians. Age of the deposit was determined by the accumulated planktonic foraminifera assemblage. The taphonomic charac- terization of the conserved entities suggests processes such as mineralization, recrystallization, sedimentary infilling, disarticulation, fragmentation, encrustation and others, indicating that these conserved entities are alocthonous and have suffered intense processes of transport, taphonomic reelaboration and resedimentation. The depositional sequence was accumulated in association with a slope, in a bathyal environment, influenced by strong precipitations, typical of tropical to subtropical latitudes. Este trabajo se enfoca en el estudio tafonómico y paleontológico de invertebrados en la turbidita de edad Paleoceno Superior - Eoceno Inferior, perteneciente a la Fm Vertientes, en Ciego de Ávila, Cuba Central. La sección estratigráfica está constituida por rocas interestratificadas detríticas, con litoclastos y bioclastos heterogéneos. Se iden- tificaron entidades conservadas de moluscos bivalvos, gastrópodos, equinodermos, corales, briozoos, fragmentos de crustáceos e icnofósiles, y abundantes invertebrados pequeños: macroforaminíferos, ostrácodos y radiolarios. Además, la edad del depósito se determinó con la asociación acumulada de foraminíferos planctónicos. La caracterización ta- fonómica de la asociación conservada permitió identificar procesos de mineralización, recristalización, rellenamiento, desarticulación, fragmentación, encostramiento, y otros, sugiriendo que la mayoría de los elementos registrados son alóctonos y que han sufrido ...